Pengembangan Sistem untuk Memonitor Aktivitas Media Sosial Berbasis Web (Studi Kasus Media Sosial Twitter Calon Legislatif pada Pemilihan Legislatif 2019) - Vasha Farisi Sarwan Halim; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Social media has been assessed to be an effective media for campaign and the use of social media is evidently could develop electability of political candidate. However, because there is limitation of time to keep monitor the condition of social media, usually political candidate's social media end up unmonitored and also not managed very well. To solve the problem, this study will build a system to monitor social media activity by applying waterfall development model with object oriented approach. This system will provide features such as displaying social media activity, people's sentiment analysis, recommendation activity to manage social media, and Indonesian trending topic. System will be developed with Model View Controller (MVC) concept with Laravel framework and PHP, HTML, Javascript as the programming languages. When implementation phase is finished, white box and black box testing is done with result the system has been 100% valid. Usability testing by heuristic evaluation method also done to make sure that system is already made easy for users. The result of usability testing is system has visibility of system status and user control and freedom problem with severity ratings valued 1 which means there is no need to change the system and the system is already made easy for users.